Evaluation of Proteasome Inhibitors in the Treatment of Idiopathic Pulmonary Fibrosis - I-Chen Chen; Yi-Ching Liu; Yen-Hsien Wu; Shih-Hsing Lo; Zen-Kong Dai; Jong-Hau Hsu; Yu-Hsin Tseng (Cells, 2022)
Idiopathic pulmonary fibrosis (IPF) is the most common form of idiopathic interstitial pneumonia, and it has a worse prognosis than non-small cell lung cancer. The pathomechanism of IPF is not fully understood, but it has been suggested that repeated microinjuries of epithelial cells induce a wound healing response, during which fibroblasts differentiate into myofibroblasts. These activated myofibroblasts express α smooth muscle actin and release extracellular matrix to promote matrix deposition and tissue remodeling. Under physiological conditions, the remodeling process stops once wound healing is complete. However, in the lungs of IPF patients, myofibroblasts re-main active and deposit excess extracellular matrix. This leads to the destruction of alveolar tissue, the loss of lung elastic recoil, and a rapid decrease in lung function. Some evidence has indicated that proteasomal inhibition combats fibrosis by inhibiting the expressions of extracellular matrix proteins and metalloproteinases. However, the mechanisms by which proteasome inhibitors may protect against fibrosis are not known. This review summarizes the current research on proteasome inhibitors for pulmonary fibrosis, and provides a reference for whether proteasome inhibitors have the potential to become new drugs for the treatment of pulmonary fibrosis.